Law, justice and social change - Saxena, D. R., 1943- (New Delhi : Deep & Deep publications, 1996)
Contributed articles.
Dr. Rohimi/Rastech
Includes bibliographical references and index.
Keywords: Sociological jurisprudence; Law reform -- India; Social change; Social justice